Two species of Megaphragma (Hymenoptera Trichogrammatidae), egg-parasitoids of Heliothrips haemorrhoidalis Bouché (Thysanoptera) in southern ltaly, with description of a new species (Bollettino di zoologia agraria e bachicoltura, 2024)
Two species of Megaphragma Timberlake (Hymenoptera Trichogrammatidae) are recorded as egg-parasitoids of Heliothrips haemorrhoidalis Bouché (Thysanoptera) in southern Italy (Thysanoptera), one of which is new and described as Megaphragma amalphitanum Viggiani.
Keywords: Megaphragma amalphitanum; Megaphragma mymaripenne; Megaphragma priesneri; Viburnum tinus